Strategies for the improvement of research competences in the professional training of engineers (2021)
The objective of this study is proposing strategies to strengthen research competencies needed by engineers in training. An analytical, situation research was conducted in four Engineering programs from a public university located in the municipality of Valledupar, Cesar Department, in Colombia. A Likert-scale questionnaire of 50 items was designed; while a document, review was performed applying a matrix that systematized the information about the study plan. Ten experts and five experts respectively validated the content of the questionnaire and of the matrix. The interpretation of the data evidenced that the greatest deficiencies of students were methodological competencies such as “result analyses”. They lack foundations on the use and interpretation of data, which hinders data processing for disseminating results, conclusions and recommendations in research reports. It is therefore necessary to transform the curriculum, including better teaching, pedagogical and didactic methods.